PERAN GURU AHLI DAN ORANG TUA DALAM PENERAPAN METODE TALAQQI PADA PROGRAM TAHFIDZ ANAK USIA DINI DI LPQ AL HIDAYAH KOTABARU - Dewi Zakiyatul Asykia; Agus Darwanto; Mega Satria (Berajah Journal, 2026)
The Qur'an for Muslims is not merely a holy book to be read, but a guide to life whose authenticity is preserved through the tradition of memorisation (tahfidz). This tradition has been practised since the time of the Prophet Muhammad SAW until today. Instilling a love for and ability to memorise (Zulfikar, 2024). The Talaqqi method is a memorisation technique that has been used since the time of the Prophet and remains relevant today. This approach brings teachers and students together and encourages active interaction during the process of memorising the Qur'an (Nurzulaikha, 2019). Memorising the Qur'an at an early age can have a significant impact on the lives of Muslims. Every child is unique and has a different learning speed, so there is no need to compare the abilities of one child with another (Suma'at, Rahendra Maya, 2020). Early childhood is a very important period in an individual's development. This period is marked by the emergence of all the crucial phases that form the basis of a person's life until the next stage of development (Lukman & Mulyati, 2021). Early childhood is the most important period to begin memorising the Qur'an (Ainia et al., 2021). In children's learning development, parenting and the role of parents are very important in nurturing children's potential, advancing the quality of early childhood education, and supporting children's growth to the maximum. (Rijkiyani, 2022). Teachers or educators have a very strategic and central position in educational activities. They require intelligence, maturity, moral integrity, sincerity, and much more. Given the importance of the position of teachers or educators in carrying out their duties of educating and teaching students, it is necessary to understand the role of teachers in the perspective of Islamic education in order to obtain a comprehensive picture of the importance of the duties of a teacher, teacher competence, and the characteristics that a teacher must possess. (Nashihin, 2021). Success in memorising the Qur'an at an early age is not merely the result of repetition techniques, but the fruit of the guidance of an expert teacher who has mature knowledge and experience. Expert teachers ensure that children do not memorise because of pressure, but because of love (Mahabbah), so that the Qur'an becomes an identity that remains with them until the end of their lives. This study proves that the ‘Talaqqi’ method is very effective for young children. This method successfully maintains a close relationship between children and teachers and students, so that children can learn enthusiastically and with love for the Qur'an.